Accuracy of 3D printing compared with milling: a multi-center analysis of try-in dentures - Herpel, Christopher; Finke, Dominic; Kühle, Reinald; Rues, Stefan; Lux, Christopher J.; Rammelsberg, Peter; Schwindling, Franz Sebastian (Journal of dentistry, 2021)
Objectives - In recent years, computer-aided design/computer-aided manufacturing (CAD/CAM) has been used to produce removable complete dentures. Most workflows include fabrication of milled or 3D-printed try-in prostheses. 3D-printing accuracy is affected by laboratory-specific and operator-dependent factors. This international five-center study sought to compare the accuracy of 3D-printed and milled try-in dentures. - Methods - The construction file of a maxillary removable complete denture was selected as a reference. Eight try-in dentures were 3D printed at each of the five centers. Each center used their own printer (Objet260 Connex, Stratasys; MAX, Asiga; Anycubic Photon, Anycubic 3D; PRO2, Asiga and cara Print 4.0, Kulzer) along with their own material, printing settings, post-processing and light-curing parameters. At center 2, eight try-in dentures were milled to serve as a benchmark (PrograMill PM7, Ivoclar Vivadent). Dentures were scanned and aligned to the reference file using best-fit algorithms. Geometric accuracy was analyzed using the root mean square value (trueness) and standard deviation (precision) of the distributed absolute mesh deviations. Mean values of the five sets of printed dentures and the single set of milled dentures were compared. - Results - Milled dentures showed a mean trueness of 65±6μm and a mean precision of 48±5μm. Thus, they were significantly more accurate than the 3D-printed dentures in four out of five centers. In mean absolute numbers, 3D printing was less true than milling by 17-89μm and less precise by 8-66μm. - Conclusions - Although milling remains the benchmark technique for accuracy, differences between milled and 3D-printed dentures were non-significant for one printing center. Furthermore, the overall performance of 3D printing at all centers was within a clinically acceptable range for try-in prostheses. - Clinical significance - The accuracy of 3D printing varies widely between and within laboratories but nonetheless lies within the range of accuracy of conventional manufacturing methods.